(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In 1999, in the city of Bahía Blanca, Argentina, one of the so-called “truth trials” began.This work analyses the strate- gies deployed by the retired and active military who testified in this trial about their actions during the repression in the last military dictatorship, aiming to investigate how they fa- ced the citation. To do this, we focus on the characteristics, actors and conflicts that were raised around this new moda- lity of justice. In this work we used different sources of information such as interviews with judges and lawyers of human rights orga- nizations, as well as presentations and court sentences and all the videos showing the hearings of the “Truth Trial” in Bahía Blanca.